Removal of E110 from Aqueous Solution Using Heat-Activated Persulfate - Lahmar, N.; Djehiche, M.; Bachiri, M. (Karagandy University of the name of academician E.A. Buketov, 2024)
This paper presents an investigation into the efficiency of heat-activated persulfate (PS) in decolorizing E110 with a focus on the influence of several parameters. The decolorization efficiency was observed to increase with rising PS concentration (no linear correlation was identified), Cl−, temperature, and time. However it was noted to decrease with rising initial dye concentration, pH, ion radius and NO2 −. The rest of the water matrix components (CO3 2−, HPO4 2−, HCO3 −, and NO3 −) did not significantly impact on the degradation of E110 at 10−3 M. Among the metal ions used (Fe2+, Ni2+, Co2+, Cu2+, and Ag+), iron and silver ions exhibited the greatest efficacy in activating PS through catalysis. A direct reaction between E110 and PS was not observed, as is the case with some anionic dyes, instead its degradation occurs via sulfate radicals (SRs) and other secondary mechanisms. The results of biological and chemical oxygen demand measurements indicate that E110 is not biodegradable. The kinetic activation parameters (Ea, ΔH≠, ΔS≠, ΔG≠) were calculated using Arrhenius and Eyring’s equations. The results obtained were as follows: 155.4 kJ mol−1, 152.7 kJ mol−1, 0.14 kJ K−1, 108.5 kJ mol−1. Finally, a preliminary mechanism for the degradation of E110 by SR has been proposed, in which the destruction of aromatic ring structures accompanies the discoloration of E110.
Keywords: E110; persulfate; sulfate radical; dye decolorization; kinetic activation parameters; mechanism; heat-activated persulfate; aqueous solution; biodegradable